1981
DOI: 10.1128/jb.146.2.676-683.1981
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of leucine-containing peptides in Escherichia coli caused by circumvention of leucine transport regulation

Abstract: Gly, inhibited the growth of a prototrophic strain of Escherichia coli K-12 at concentrations between 0.05 and 0.28 mM. Toxicity requires normal uptake of peptides. When peptide transport was impaired by mutations, strains became resistant to the respective LCP. Inhibition of growth occurred immediately after the addition of LCP, and was relieved when 0.4 mM isoleucine was added. The presence of Gly-Leu in the medium correlated with the inhibition of growth, and the bacteria began to grow at the normal rate 70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 11 publications
2
15
0
Order By: Relevance
“…The addition of Ala-Leu to the culture of wild-type MG1655 increased the lag period by more than 10 h regardless of the presence of ammonium sulphate in the medium ( Fig. 1; data not shown for the growth in the absence of ammonium sulphate), as expected from a previous report (Tavori et al ., 1981). The ptsP mutant (CR101) exhibited a phenotype of significantly faster growth than its parental strain MG1655 in the presence of the dipeptide, confirming the PM data.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The addition of Ala-Leu to the culture of wild-type MG1655 increased the lag period by more than 10 h regardless of the presence of ammonium sulphate in the medium ( Fig. 1; data not shown for the growth in the absence of ammonium sulphate), as expected from a previous report (Tavori et al ., 1981). The ptsP mutant (CR101) exhibited a phenotype of significantly faster growth than its parental strain MG1655 in the presence of the dipeptide, confirming the PM data.…”
Section: Resultssupporting
confidence: 89%
“…It was previously reported that a variety of LCPs inhibited the growth of a prototrophic strain of E. coli K-12 in minimal medium by increasing the lag period by up to 10 h; after the lag period, the rate of growth was similar to the control culture grown in the absence of LCPs (Tavori et al, 1981). It was shown that the concentration of leucine inside bacteria treated with LCPs was higher than that in the leucine-treated or the control cultures and proposed that the growth inhibition by LCPs was due to accumulation of abnormally high concentrations of leucine in the cell, although the mechanism by which LCPs led to high intracellular leucine has not yet been clarified.…”
Section: Toxicity Of Lcps Is Due To Leucine and The Dephospho-form Ofmentioning
confidence: 78%
“…To ascertain whether or not pCH1 confers a general increase in peptide uptake, the plasmid was transformed into a variety of E. coli auxotrophs: in many cases growth on peptides containing the required amino acid was enhanced (data not shown). In addition, Table 4 shows that pCH1 renders cells sensitive to valineor leucine-containing peptides, presumably causing an increase in peptide uptake, followed by release of free amino acids which, in sufficient concentrations, can interfere with isoleucine biosynthesis (38). To confirm this we showed that isoleucine can specifically overcome the toxic effects of leucine-containing peptides.…”
Section: Resultsmentioning
confidence: 71%
“…Leucine‐containing peptides inhibited the growth of a wild‐type strain (MG1655) of E. coli K‐12 in minimal medium by increasing the lag period by up to 10 h (Tavori et al ., 1981) and the ptsN mutation increases the lag time more than five times in a medium containing the same concentration of an LCP (Lee et al ., 2005). As deletion of rpoS suppresses the extreme LCP sensitivity of the ptsN mutant (Fig.…”
Section: Resultsmentioning
confidence: 99%